A Material Model of Particle Size Dependent Transformation Plasticity of PSZ Ceramics under Thermomechanical Loading. Issue 7 (17th July 2013) - Mehlhorn, Lars; Mühlich, Uwe; Kuna, Meinhard; Biermann, Horst
<x xml:space="preserve">Abstract</x> In this article a material model of transformation plasticity in PSZ materials is presented. It features a crystallite size dependent phase transition criterion and nonlinear strain‐temperature behaviour with hysteresis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>